2019
DOI: 10.1155/2019/6958643
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Fragility Analysis of High Earth‐Rockfill Dams considering the Number of Ground Motion Records

Abstract: This study analyzes the impact of the number of ground motions on the seismic fragility of a high earth-rockfill dam and the estimation of reasonable fragility parameters based on a sufficient number of earthquake records. In this paper, the vertical deformation is obtained using the three-dimensional finite element program DYNE3WAC combined with the Pastor–Zienkiewicz–Chan model and Biot dynamic consolidation theory. The relative seismic settlement rate is considered the damage index for the seismic fragility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Presently, the number of seismic analytical fragility functions for earth dams is very limited and always based on input selections performed using uniform hazard spectra (UHS) (e.g. Jin and Chi, 2019; Vecchietti et al, 2019, both for rockfill dams). Table 1 summarizes the main studies on fragility functions on some infrastructure systems, for different DM and IM; the dispersion β is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the number of seismic analytical fragility functions for earth dams is very limited and always based on input selections performed using uniform hazard spectra (UHS) (e.g. Jin and Chi, 2019; Vecchietti et al, 2019, both for rockfill dams). Table 1 summarizes the main studies on fragility functions on some infrastructure systems, for different DM and IM; the dispersion β is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, fragility curves have mostly been obtained for concrete and arch dams [1,2,3,4]. A few studies, recently published, refer to large earth dams, mainly concrete-faced rockfill dams (CFRDs) [5,6,7], earth-rockfill dams [8], rockfill dams with concrete core [9,10] and just one study (in the authors' knowledge) concerns tailing dams [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cimellaro et al [40] researched the sensitivity of the number of earthquake records using an MDOF inelastic shear-type building and concluded that using 23 ground motions can obtain the accurate estimation of parameters in fragility functions when PGA is IM. Jin and Chi [41] analyzed the effect of the number of earthquake records on the seismic fragility analysis of high earth-rockfill dams. Mo et al [32] selected 28 near-field and 22 far-field ground motions as a suite.…”
Section: Introductionmentioning
confidence: 99%